2022
DOI: 10.1021/acsami.2c09120
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Nanospheres as Anti-inflammation and Antisenescence Interfacial Biolubricant for Treating Temporomandibular Joint Osteoarthritis

Abstract: The development of temporomandibular joint (TMJ) osteoarthritis is highly associated with mechanical overloading, which can result in accelerated cartilage degradation and damage due to increased interfacial friction and the release of inflammatory factors and catabolic enzymes. In the present study, we for the first time developed self-assembled drug-free nanospheres with pharmaceutical-active functions, which could be used as an intra-articularly injected biolubricant for the treatment of TMJ osteoarthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…2b, compared with water with a coefficient of friction (COF) value of 0.08, the COF values of different concentrations of CB and BB significantly reduced to ∼0.04 at 0.5 Hz, 1 N. The significantly improved lubricating performance is attributed to the zwitterionic charges (–N + (CH 3 ) 2 – and –SO 3 − ) of PSBMA brush side chains, which attracted a large number of water molecules through ionic coupling, forming a stable hydrated lubricating layer. 45,46 It should be noted that there is no significant difference between the COF values of 1 mg mL −1 and 0.25 mg mL −1 . Therefore, we selected the concentration of CB and BB at 0.25 mg mL −1 for subsequent cell and animal experiments.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…2b, compared with water with a coefficient of friction (COF) value of 0.08, the COF values of different concentrations of CB and BB significantly reduced to ∼0.04 at 0.5 Hz, 1 N. The significantly improved lubricating performance is attributed to the zwitterionic charges (–N + (CH 3 ) 2 – and –SO 3 − ) of PSBMA brush side chains, which attracted a large number of water molecules through ionic coupling, forming a stable hydrated lubricating layer. 45,46 It should be noted that there is no significant difference between the COF values of 1 mg mL −1 and 0.25 mg mL −1 . Therefore, we selected the concentration of CB and BB at 0.25 mg mL −1 for subsequent cell and animal experiments.…”
Section: Resultsmentioning
confidence: 94%
“…) of PSBMA brush side chains, which attracted a large number of water molecules through ionic coupling, forming a stable hydrated lubricating layer. 45,46 It should be noted that there is no significant difference between the COF values of 1 mg mL À1 and 0.25 mg mL À1 . Therefore, we selected the concentration of CB and BB at 0.25 mg mL À1 for subsequent cell and animal experiments.…”
mentioning
confidence: 94%
“…The lubrication dysfunction of articular cartilage is one of the primary reasons for the development of TMJ osteoarthritis, and the increased joint friction can significantly accelerate progression of osteoarthritis [ 62 , 63 ]. It has been reported that phospholipids generate excellent hydration lubrication effect, which is attributed to the hydration layers formed surrounding the positive and negative headgroups [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols are recognized as natural antioxidants because their abundant reducing phenolic hydroxyl groups transfer electrons to free radicals, thereby protecting cells from excessive free-radical erosion [86]. Zhao et al [87] designed self-assembled nanospheres (PDS) by polymerizing dopamine methacrylamide (DMA) and sulfobetaine methacrylate (SBMA) via reversible addition-fragmentation chain transfer (RAFT) reactions. The excellent radical scavenging ability of the nanospheres is caused by the catechol groups in DMA being able to donate electrons to 2-diphenyl-1picrylhydrazyl (DPPH)• and 2,2′-azino-bis (3ethylbenzothiazoline-6-sulfonic acid) (ABTS) + • to quench the oxidative radicals (figure 11(A)).…”
Section: Anti-oxidation and Anti-inflammationmentioning
confidence: 99%
“…− species in phosphatidylcholine lipids can orient a large number of free water molecules around these charges through the charge-dipole interactions to form a hydration layer [87,94]. At present, various biomimetic zwitterionic polymers, including poly (2methacryloyloxyethyl phosphocholine) (PMPC) [89,95], poly(methacrylic acid 3-sulfopropyl ester potassium salt) (PSPMA) [94], and poly(sulfomethacrylic acid betaine) (PSBMA) [87,96], have been reported to reduce the interfacial friction of the articular cartilage. However, these zwitterionic polymers face problems such as insufficient bulk density, unstable binding with cartilage tissues, and high surface roughness, which affect their lubrication performance in cartilage tissue [97].…”
Section: Joint Lubricationmentioning
confidence: 99%